PENINGKATAN PENERAPAN GEOGRAFI PERTANIAN DENGAN PEMBUATAN PESTISIDA NABATI UNTUK TANAMAN KAKAO (Theobroma cacao L ) DI KENAGARIAN LIMA KAUM KABUPATEN TANAH DATAR - ratna Wilis (JURNAL GEOGRAFI, 2013)
Cocoa or also known as chocolate is widely planted around the yard of the house .Crop Production price was very good in the market so it can help increase incomes. Lately cocoa crop production suffered many failures, especially in Kenagarian Lima Kaum, Tanah Datar Regency. The high risk of failure of cocoa crop yields caused by pests and diseases , among others : the fruit and stem borer can cause fruit to rot blackened . Besides cocoa pods are also attacked by fungus , which causes fruit rot entirely rotten and there is also a portion of the fruit . Chemical control had a negative impact on the environment and humans as well as livestock. While the use of botanical pesticides do not cause negative impacts to the human environment and animals, because these pesticides readily biodegradable and water soluble, readily available , cost less and homemade. Then the pesticide manufacturing plant is considered an appropriate choice is applied to agricultural productivity , especially in the cocoa plant back up and better welfare of the farming community .